La French Pattern Bank : un dictionnaire onomasiologique des valences à l’intention des apprenants avancés du FLE - Bürgel, Christoph; Siepmann, Dirk (Actes du Congrès Mondial de Linguistique française 2026 - 10ème Congrès Mondial de Linguistique Française)

Perspektiven angehender Lehrkräfte auf Forschendes Lernen – eine qualitative Längsschnittstudie im Referendariat und Berufseinstieg - Homt, Martina; Bloh, Bea; Wehde, Janis (Zeitschrift für Bildungsforschung)
Das hochschuldidaktische Konzept des Forschenden Lernens gilt als zentrales Element der universitären Lehrkräftebildung in Deutschland und ist in fast allen Bundesländern Bestandteil des Praxissemesters. Damit einhergehende Erwartungen im Hinblick auf den Professionalisierungsprozess von Lehrkräften fokussieren insbesondere die Vermittlung einer forschenden Grundhaltung, die auf eine nicht-wissenschaftsferne Berufsausübung abzielt. Wir fassen die forschende Grundhaltung als Professionsüberzeugung, die aus einer kognitiven, affektiven und handlungsbezogenen Komponente besteht und untersuchen die Komponenten im Zusammenspiel sowie im Längsschnitt. Mittels teilstrukturierter Interviews mit 22 angehenden Lehrkräften im Referendariat und Berufseinstieg, die sich im Praxissemester mit Forschendem Lernen befasst haben, werden das Verständnis (kognitive Komponente) und die Bedeutsamkeit (affektive und handlungsbezogene Komponente) Forschenden Lernens in der jeweiligen Ausbildungs- bzw. Berufsphase erfragt. Die Daten werden inhaltsanalytisch sowie typenbildend ausgewertet, um das Verständnis und die Bedeutsamkeit in der jeweiligen Phase, längsschnittliche Entwicklungen sowie das Verhältnis von Verständnis und Bedeutsamkeit herauszuarbeiten. Die Befunde zeigen, dass die Verständnisse von Forschendem Lernen sowohl im Referendariat als auch im Berufseinstieg variieren. Zudem ist das Konzept – laut Schilderungen der Befragten – durchaus bedeutsam für ihre Lern- und Handlungspraxis, jedoch nicht für alle und in unterschiedlich ausgeprägter Form. Die Typenbildung verdeutlicht, dass die fehlende Bedeutsamkeit Forschenden Lernens mit Fehlkonzepten einhergeht und eine höhere Bedeutsamkeit erkennbar ist, wenn Adaptionsleistungen hinsichtlich des Konzepts vorgenommen werden. Insgesamt ist im Sinne der Auffassung als Professionsüberzeugung die Anbahnung einer forschenden Grundhaltung bei einigen Befragten erkennbar. Implikationen für eine künftige Hochschulbildung ergeben sich u. a. mit Blick auf die Unterstützung von Studierenden bei Adaptionsleistungen für die (jeweilige) Praxis.

A hybrid knowledge based and data based approach for efficient clinch joint design - Einwag, Jonathan-Markus; Wiemer, Maximilian; Wartzack, Sandro; Goetz, Stefan (Discover Mechanical Engineering)
Abstract The design of clinch joints is a cost- and time-intensive iterative process due to the complex relationships between tool and process parameters and the resulting joint properties. To address this, this contribution proposes a novel hybrid workflow that combines knowledge- and data-based approaches. Relationships are categorized based on their knowledge quality and the need for a quantitative prediction. Well-established, generalizable relationships are formalized in an ontology as design guidelines (no quantification required) or SWRL rules (quantification required) to model expert knowledge. In contrast, hard-to-formalize or not-fully-understood relationships are treated with regression models for continuous or classification models for binary criteria. These approaches are combined in a generic user interface (GUI), where the ontology can be accessed using predefined SPARQL queries to select and adapt parameters using expert knowledge. These parameters are then used as input for the metamodels. The developed workflow is evaluated on two exemplary joining tasks to illustrate, how designers can retrieve similar prior joints, adapt parameters using the encoded design rules and predict resulting joint properties under varying process conditions. In summary, the combination of ontology and metamodels facilitates the transition of trial and error into an efficient, documentable design process.

Zur Einführung in den Themenschwerpunkt Lexiko-Grammatik im Fremdsprachenunterricht - Bürgel, Christoph (Fremdsprachen Lehren und Lernen (FLuL), 7-14)

Einfluss von Misch-, Material- und Prozessparametern auf die Koaleszenz flammgeschützter Pulver im Lasersintern - Peitz, Robin

A modular large language model agent architecture for adaptive and autonomous process-aware execution - Skolik, Alexander Marcus; Kaltenpoth, Sascha Benjamin; Beverungen, Daniel; Müller, Oliver (Information Systems)

Experimental and Numerical Investigation of Jump Phenomena in the Frequency Response of Piezoelectric Systems - Friesen, Olga; Hölscher, Jonas; Siegmund, Michael B. K.; Claes, Leander; Henning, Bernd

Loose Coupling of Spectral and Spatial Models for Multi-Channel Diarization and Enhancement of Meetings in Dynamic Environments - Meise, Adrian Tobias; Cord-Landwehr, Tobias; Boeddeker, Christoph; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2026 - 2026 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
Sound capture by microphone arrays opens the possibility to exploit spatial, in addition to spectral, information for diarization and signal enhancement, two important tasks in meeting transcription. However, there is no one-to-one mapping of positions in space to speakers if speakers move. Here, we address this by proposing a novel joint spatial and spectral mixture model, whose two submodels are loosely coupled by modeling the relationship between speaker and position index probabilistically. Thus, spatial and spectral information can be jointly exploited, while at the same time allowing for speakers speaking from different positions. Experiments on the LibriCSS data set with simulated speaker position changes show great improvements over tightly coupled subsystems.
Keywords: mixture models; meeting processing; diarization; source separation

What’s Next? Micro‐ and Meso‐Level Predictors of Mobility Intentions Among International Chinese Students in Germany - Bilecen, Başak; Diekmann, Isabell; Faist, Thomas (Global Networks)
**ABSTRACT** While studying abroad, international students not only pursue academic qualifications but also begin to imagine and plan their future mobility trajectories. One central decision concern is whether to remain in the host country after graduation or return to the country of origin or move to another country. This article investigates the individual and social factors that shape post‐graduation work intentions among international Chinese students in Germany, the second‐largest international student group in the country. Drawing on original survey data from the Bright Futures project (2018), we analyse how life satisfaction, romantic partnerships, career aspirations and social networks influence students’ likelihood of planning to work in Germany after graduation. Using binary logistic regression models, we find that higher life satisfaction, valuing meaningful employment and having a partner in Germany are all significantly associated with intentions to stay. In contrast, the geographical location of broader personal networks shows no significant effect. These findings contribute to migration and higher education research by foregrounding the role of subjective well‐being and certain forms of relational embeddedness in shaping students’ imagined futures. Rather than treating international students as passive participants in education‐driven mobility, we highlight how personal and emotional factors influence their transition into potential long‐term migrants.

An unholy trinity: TFNP, polynomial systems, and the quantum satisfiability problem - Aldi, Marco; Gharibian, Sevag; Rudolph, Dorian (17th Innovations in Theoretical Computer Science Conference (ITCS 2026))
The theory of Total Function NP (TFNP) and its subclasses says that, even if one is promised an efficiently verifiable proof exists for a problem, finding this proof can be intractable. Despite the success of the theory at showing intractability of problems such as computing Brouwer fixed points and Nash equilibria, subclasses of TFNP remain arguably few and far between. In this work, we define two new subclasses of TFNP borne of the study of complex polynomial systems: Multi-homogeneous Systems (MHS) and Sparse Fundamental Theorem of Algebra (SFTA). The first of these is based on B\'ezout's theorem from algebraic geometry, marking the first TFNP subclass based on an algebraic geometric principle. At the heart of our study is the computational problem known as Quantum SAT (QSAT) with a System of Distinct Representatives (SDR), first studied by [Laumann, L\"auchli, Moessner, Scardicchio, and Sondhi 2010]. Among other results, we show that QSAT with SDR is MHS-complete, thus giving not only the first link between quantum complexity theory and TFNP, but also the first TFNP problem whose classical variant (SAT with SDR) is easy but whose quantum variant is hard. We also show how to embed the roots of a sparse, high-degree, univariate polynomial into QSAT with SDR, obtaining that SFTA is contained in a zero-error version of MHS. We conjecture this construction also works in the low-error setting, which would imply SFTA is contained in MHS.

The role of the mathematics textbook in times of resource diversity - Stallmeister, Lea; Rezat, Sebastian (Educational Studies in Mathematics)
Abstract Mathematics textbooks used to be the key resource for students’ self-regulated learning of mathematics. Primarily due to the digitalization of society, students have potentially greater access to a wider range of resources such as internet search engines, learning platforms, educational videos, and Generative AI. This study investigates the role of the mathematics textbook in comparison to other resources within students’ self-regulated learning practices. Data were collected via a survey of 1101 German secondary students, representing three school types ( Gymnasium , Gesamtschule , Realschule ) and three grade levels (6, 9, and upper secondary). The questionnaire assessed the frequency of resource use in and outside class, reasons and purposes of use, and resource-based strategies when facing learning challenges outside class. Results show that the printed mathematics textbook is the most frequently used resource both in class and outside class. The textbook remains the most relevant resource for key purposes, such as an aid for doing homework and preparing for tests and exams. However, its dominance diminishes with age: in upper secondary school, students increasingly rely on self-created notes, and online resources. Correlation analyses reveal moderate to strong links between in-class and out-of-class use, suggesting an association between resource use and classroom culture. The findings underscore the textbook’s enduring centrality as a foundational, trusted resource within a dynamic and increasingly diverse learning environment. This study calls for pedagogical approaches that integrate textbooks more intentionally within broader resource systems, supporting students’ agency and strategic resource selection in an era of digital abundance.
Keywords: mathematics; textbooks; userstudy; resources; digital resources; students; secondary eduction

Fiber-matrix adhesion in glass fiber reinforced thermoplastic composite laminates and its effect on mechanical properties - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Haag, Markus; Gries, Thomas; Henning, Bernd (International Polymer Processing)
With the growing demand for lightweight solutions to reduce emissions, especially in the transportation, automotive and aerospace sectors, recyclable, continuous fiber-reinforced plastic composite laminates with a thermoplastic matrix are of rising interest. To achieve their maximum mechanical properties, the fiber-matrix adhesion (FMA) is critical. In this work, continuous fiber-reinforced thermoplastic laminates (CFRTPL) with a polypropylene (PP) matrix and twill woven glass fiber fabrics are produced by film stacking. The films used contain different amounts of maleic-anhydride-grafted PP (MA-g-PP) as a coupling agent to produce CFRTPL of different mechanical strengths. To analyze the FMA, the CFRTPL are subjected to Charpy-impact and tensile tests. Additionally, single fiber pull-out tests (SFPT) are conducted to further investigate the effect of MA-g-PP on the FMA. The results of the SFPT show an improvement in apparent interfacial shear strength (AIFSS) when the MA-g-PP content is increased, which can be attributed to an increase in FMA. However, the research shows that MA-g-PP has a low impact on the mechanical properties if the force is applied parallel to the warp and weft threads during tensile testing and the results of the Charpy-impact testing suffer from embrittlement of the matrix material. Subsequently, the results of this study are compared to three-point flexural tests conducted in a previous study. It can be concluded that tensile and impact tests are not suited to investigate FMA on a macroscopic scale, while SFPT and flexural tests provide a better alternative.

The role of the mathematics textbook in times of resource diversity - Stallmeister, Lea; Rezat, Sebastian (Educational Studies in Mathematics)
Mathematics textbooks used to be the key resource for students’ self-regulated learning of mathematics. Primarily due to the digitalization of society, students have potentially greater access to a wider range of resources such as internet search engines, learning platforms, educational videos, and Generative AI. This study investigates the role of the mathematics textbook in comparison to other resources within students’ self-regulated learning practices. Data were collected via a survey of 1101 German secondary students, representing three school types (Gymnasium, Gesamtschule, Realschule) and three grade levels (6, 9, and upper secondary). The questionnaire assessed the frequency of resource use in and outside class, reasons and purposes of use, and resource-based strategies when facing learning challenges outside class. Results show that the printed mathematics textbook is the most frequently used resource both in class and outside class. The textbook remains the most relevant resource for key purposes, such as an aid for doing homework and preparing for tests and exams. However, its dominance diminishes with age: in upper secondary school, students increasingly rely on self-created notes, and online resources. Correlation analyses reveal moderate to strong links between in-class and out-of-class use, suggesting an association between resource use and classroom culture. The findings underscore the textbook’s enduring centrality as a foundational, trusted resource within a dynamic and increasingly diverse learning environment. This study calls for pedagogical approaches that integrate textbooks more intentionally within broader resource systems, supporting students’ agency and strategic resource selection in an era of digital abundance.

The CP2K Program Package Made Simple - Iannuzzi, Marcella; Wilhelm, Jan; Stein, Frederick; Bussy, Augustin; Elgabarty, Hossam; Golze, Dorothea; Hehn, Anna-Sophia; Graml, Maximilian; Marek, Stepan; Gökmen, Beliz Sertcan; Schran, Christoph; Forbert, Harald; et al. (The Journal of Physical Chemistry B)

All a question of the goal? Re-tracing (mis)alignments between teachers’ implementations of curriculum material and intended learning goals in the context of early childhood educator training in Germany - Richter, Alix; Bruns, Julia (International Electronic Journal of Mathematics Education)
Curriculum material is often designed to address content-specific intended learning goals. However, research indicates that teachers’ personal goals may cause misalignments between their implementation of curriculum material and its intended learning goals. This study aims to investigate misalignments between teachers’ implementation of curriculum material and its intended learning goals and to which extent they are caused by teachers’ personal goals. To reach this aim, a qualitative study was conducted to examine how eight vocational school teachers implemented the learning activity “How many?” suggested for the initial training of early childhood educators on the topic of set perception and determination of cardinality. Each participant provided a lesson plan and self-recorded lesson video on the topic of set perception and determination of cardinality. In addition, participants were interviewed on how they used the provided curriculum material for designing their lessons and their potential reasons to adapt or omit “How many?”. To evaluate their lesson design’s alignment with the activity’s intended learning goals, the participants' lesson plans were analyzed using qualitative content analysis. Triangulation of the findings with the interview data revealed that only one participant fully adopted the intended learning goals as her own and implemented the activity completely in line with its intended learning goals. Meanwhile, the remaining participants’ personal goals, such as reducing math anxiety, seemed to cause misalignments regarding the intended learning goals. The study's results detail further constraints and affordances to the alignment between teachers’ lesson designs and learning goals intended by curriculum material. It is followed that it is central to support teachers in adopting intended learning goals as their personal goals. Otherwise, teachers’ classroom implementation of curriculum material may not suffice to reach desired outcomes.

Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven
Eine zentrale Herausforderung in der Professionalisierung pädagogischer Fach- und Lehrkräfte besteht in der Relation von eher theoretischen und praktischen Ausbildungsbestandteilen. Beispielsweise fühlen sich angehende Lehrkräfte durch ihr Studium häufig nicht ausreichend auf die beruflichen Anforderungen vorbereitet. Daher wird verstärkt versucht, Curricula von Ausbildungs- und Studiengängen deutlicher an den tatsächlichen professionellen Handlungsanforderungen zu orientieren und auch in frühen Ausbildungsphasen verstärkt Elemente beruflicher Praxis zu integrieren. Dieser Band nimmt die Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften theoretisch-konzeptionell sowie empirisch in den Blick. Zudem werden innovative Lehransätze aufgezeigt, die den Fokus auf eine Stärkung einer solchen Handlungsorientierung legen, z.B. durch simulationsbasierte Lern- und Prüfungsformate. Es handelt sich um den zweiten Band der Reihe Paderborner Beiträge zur Bildungsforschung und Lehrkräftebildung, die von der PLAZ – Professional School of Education herausgegeben wird.

A functionalization-free plasmonic hole-sphere nanogap SERS platform for reliable on-site analysis and oxide-state classification - Kim, Minjun; Heo, Damun; Cho, Sung Yoon; Lee, Ye-Won; Gu, Sun-Hwa; Adhikari, Samir; Lee, Donghan; Jeong, Seok Soon; Kim, Hyuck Soo; Devaraj, Vasanthan; Zentgraf, Thomas; Jeon, Min Yong; et al. (Nanoscale)
A functionalization-free plasmonic nanogap platform enables reliable on-site SERS based oxidation-state differentiation of arsenic through uniform metal-vacuum-metal cavities with high electromagnetic enhancement and minimal background interference.

Psychologie studieren - Scharlau, Ingrid; Buhl, Heike M.
Worum geht es eigentlich in einem Psychologiestudium? Wie ist das Studium aufgebaut? Und wie lässt es sich am besten meistern? Dieses Buch bietet eine Einführung in die Grundlagen, Felder und Themen der Psychologie und gibt Tipps für einen erfolgreichen Einstieg in das Studium und Freude am Fach. Das Buch ist perfekt geeignet für diejenigen, die vor der Entscheidung einen Einblick in das Psychologiestudium gewinnen oder sich in den ersten Semestern orientieren möchten.

Smart drug delivery systems for potential targeted cancer therapy: Exploiting increased glutathione levels in tumor microenvironments - Kramer, Maurice; Horky, Corinna; Völlmecke, Katharina; Mulac-Hahnen, Dennis; Herrmann, Fabian; Kuckling, Dirk; Langer, Klaus (Next Nanotechnology)
Over the past decades, nanoparticulate drug carrier systems have emerged as promising tools in medicine. A persistent challenge in current pharmacotherapy is the limited selectivity of active pharmaceutical ingredients, resulting in undesirable side effects. Smart drug delivery systems, which release encapsulated active pharmaceutical ingredients in response to specific stimuli, offer a potential solution by enabling controlled drug release. This approach can be particularly relevant for exploiting biochemical differences between extracellular and intracellular environments. In this study, self-immolative polydisulfide based polymers manufactured from dithiothreitol were processed into nanoparticle formulations to respond preferentially to elevated glutathione levels, which are characteristic of intracellular environments and are often increased in tumor cells. The influence of polymer chain length on the physicochemical properties of the resulting nanoparticles was investigated. Lumogen® Red was incorporated as a model substance to determine the loading capacity of the carrier system. Degradation was characterized using dynamic light scattering and asymmetric flow field-flow fractionation, as well as by imaging techniques such as atomic force microscopy. Selective release of the embedded substance was demonstrated at elevated glutathione concentrations, while no significant release was observed at extracellularly relevant levels (10 µM glutathione), where the behavior was comparable to the buffer control. Increased release was observed under intracellularly relevant conditions (2 – 10 mM glutathione). These findings support a redox-responsive behavior under intracellular-like conditions. The latter was proven for primary fibroblasts and the cancer cell lines BT-474, MCF-7 and SK-BR-3 by quantification of intracellular low molecular weight thiols. The nanoparticle uptake was confirmed in the investigated cell lines by visualization via confocal laser scanning microscopy. Via lysosomal staining it was shown that nanoparticles accumulate in lysosomes. Furthermore, the carrier system itself showed no cytotoxic properties in cell culture studies against the four different cell types. The developed system is a suitable and very promising smart drug delivery system in the context of controlled drug release.
Keywords: Nanoparticles; Smart drug delivery; Controlled release; Self-immolative polymers; Tumor targeting

Opportunities and obstacles for industrial applications - Schlüter, Alexander; Krogbäumker, Luisa; Böse, Kevin; Riese, Julia (Hydrogen and Bioenergy)